Analisis Performa Dan Optimasi Bandwidth Jaringan Wifi Di Lingkungan Kampus - Angga Novita Prasetyo Ningrum; Binastya Anggara Sekti (Prosiding SISFOTEK, 2024)
WiFi networks have become critical components in supporting academic and administrative activities in higher education institutions. Esa Unggul University, as a growing educational institution, faces challenges in ensuring the quality and reliability of its WiFi network as the number of users and bandwidth requirements increase. This study analyses the performance and optimises the bandwidth of the WiFi network in the Esa Unggul University environment. Through a qualitative approach with a case study, this research collects data through in-depth interviews, direct observations, and technical measurements. Analysis is conducted on access speed, connection stability, and bandwidth capacity in various campus areas. The research results identify several critical points affecting network performance and propose optimisation strategies that include infrastructure upgrades, configuration adjustments, and implementation of effective bandwidth management. The findings and recommendations from this study are expected to improve the quality of internet service at Esa Unggul University, better support academic and administrative activities, and provide valuable insights for other higher education institutions in managing their WiFi network infrastructure.